Społeczno-demograficzne czynniki warunkujące pozytywne postawy wobec imigrantów. Badanie przekrojowe wśród osób mających kontakt z imigrantami z racji pełnionych funkcji zawodowych - Niewiadomska, Iwona; Jurek, Krzysztof; Wośko, Patrycja (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
This article discusses attitudes towards immigrants demonstrated by professionals who are in contact with them by virtue of their professional obligations. The article is both theoretical and practical in nature since intense negative attitudes towards immigrants can have far-reaching consequences for the hosts and the received. The study group consisted of teachers, health care professionals and uniformed services (border guards and prison guards). The cross-sectional survey was conducted using the author’s own tool for the diagnosis of attitudes towards migrants (Questionnaire of Attitudes towards Migrants, QATM). The research covered 347 people. Its aim was to identify the determinants of positive attitudes towards immigrants. The results indicate that the positive drivers are gender, intensity of contact, place of residence, age, having children and education.